2022
DOI: 10.1155/2022/3846217
|View full text |Cite
|
Sign up to set email alerts
|

HO-1 Contributes to Luteolin-Triggered Ferroptosis in Clear Cell Renal Cell Carcinoma via Increasing the Labile Iron Pool and Promoting Lipid Peroxidation

Abstract: Ferroptosis, a novel form of regulated cell death characterized by disrupted iron metabolism and the accumulation of lipid peroxides, has exhibited enormous potential in the therapy of cancer particularly clear cell renal cell carcinoma (ccRCC). Luteolin (Lut), a natural flavonoid widely existing in various fruits and vegetables, has been proven to exert potent anticancer activity in vitro and in vivo. However, previous studies on the anticancer mechanism of Lut have been shown in apoptosis but not ferroptosis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(32 citation statements)
references
References 56 publications
0
32
0
Order By: Relevance
“…HO-1 overexpression has been demonstrated as a mechanism of resistance and malignancy progression in cancer cells; however, it has been demonstrated that low levels of HO-1 are associated with an increased risk of metastasis in oral and tongue squamous cell carcinoma, together with a significant presence of undifferentiated cells [ 44 ]. Additionally, data analysis by Han et al showed that low expression levels of HO-1 in renal carcinoma predicted poor prognosis, which might be improved by activating ferroptosis through the induction of HO-1 [ 45 ]. Furthermore, overexpression of HO-1 in prostate cancer cells resulted in markedly reduced cell proliferation and migration [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…HO-1 overexpression has been demonstrated as a mechanism of resistance and malignancy progression in cancer cells; however, it has been demonstrated that low levels of HO-1 are associated with an increased risk of metastasis in oral and tongue squamous cell carcinoma, together with a significant presence of undifferentiated cells [ 44 ]. Additionally, data analysis by Han et al showed that low expression levels of HO-1 in renal carcinoma predicted poor prognosis, which might be improved by activating ferroptosis through the induction of HO-1 [ 45 ]. Furthermore, overexpression of HO-1 in prostate cancer cells resulted in markedly reduced cell proliferation and migration [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, this activity dependent increase of ROS will induce lipid peroxidation of cell membrane and damage the healthy tissue, thus aggravating muscle fatigue during strenuous exercise (Dillard et al, 1978;Alessio et al, 1988). Therefore, ferroptosis may be a new type of cell death that participates in the physiological and pathological process of EEIF except apoptosis (Sun Y. et al, 2016;Liu S. et al, 2022). Excitingly, a recent report explored the relationship between ferroptosis and EEIF (Xiao et al, 2022).…”
Section: Ferroptosis and Exhaustive Exerciseinduced Fatiguementioning
confidence: 99%
“…Therefore, the maintenance of systemic iron homeostasis requires the maintenance of a normal heme metabolism. The up-regulation of heme oxygenase 1 (HO-1), a crucial enzyme that degrades heme to liberate iron, can participate in ferroptosis induction by increasing intracellular iron levels ( Tenhunen et al, 1968 ; Han et al, 2022 ). HO-1 inhibitor zinc protoporphyrin IX was discovered to counteract erastin-induced ferroptosis in HT-1080 fibrosarcoma cells ( Kwon et al, 2015 ).…”
Section: The Regulatory Mechanism Of Ferroptosismentioning
confidence: 99%
“…By reacting with polyunsaturated lipids (LH), hydroxyl radicals generate lipid peroxyl radicals, and arachidonate lipoxygenases (ALOXs) can also oxidize LH into hydroperoxide (LOOH), which is then converted into lipid peroxyl radical by Fenton reaction. Eventually, the lipid peroxyl radicals initiate and facilitate lipid peroxidation [ 15 , 16 ]. Moreover, iron can enhance the activity of lipoxygenases (ALOXs) and cytochrome P450 oxidoreductase (POR), which are metabolic enzymes associated with phospholipid peroxidation ( Figure 2 ).…”
Section: Mechanisms Governing Ferroptosismentioning
confidence: 99%